2016
DOI: 10.1371/journal.pone.0166517
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Influenza Vaccination Coverage between Adult Immigrants and Italian Citizens at Risk for Influenza-Related Complications: A Cross-Sectional Study

Abstract: BackgroundDue to their increased vulnerability, immigrants are considered a priority group for communicable disease prevention and control in Europe. This study aims to compare influenza vaccination coverage (IVC) between regular immigrants and Italian citizens at risk for its complications and evaluate factors affecting differences.MethodsBased on data collected by the National Institute of Statistics during a population-based cross-sectional survey conducted in Italy in 2012–2013, we analysed information on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 18 publications
3
23
0
2
Order By: Relevance
“…Our study showed a reduced level of vaccination against flu among migrants, particularly in Italy. This difference was more apparent among non- EU citizens and this result is in line with previous findings from Spain [ 35 ] and Italy [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed a reduced level of vaccination against flu among migrants, particularly in Italy. This difference was more apparent among non- EU citizens and this result is in line with previous findings from Spain [ 35 ] and Italy [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, it could also be due to unwillingness to use services for cultural, religious or other reasons [ 6 , 34 ]. This is why providing culturally sensitive information, training health professionals in culturally competent service delivery, and engaging key individuals from the migrant community to promote immunization could be important to meet health needs of immigrants and overcome informal barriers to immunization [ 34 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Migrants do not specifically represent a risk of spreading influenza to receiving countries [25]. Nonetheless, migrants are more susceptible to influenza in part due to lower levels of vaccine coverage [26, 27]. Infection may be transmitted by droplet, aerosol, or contact [28].…”
Section: Viral Infectionsmentioning
confidence: 99%